Flash non-woven fabric as well as preparation method and application thereof

By adjusting the component ratio of flash nonwoven fabrics and the surface hydroxyl content of modified calcium carbonate, the problem of insufficient mechanical strength and waterproofing performance of flash nonwoven fabrics in the prior art is solved, and high breathability and mechanical strength are achieved The flash non-woven fabric with waterproof performance improves its reuse rate and ethylene oxide analytical efficiency in the medical packaging field.

CN119287585AActive Publication Date: 2025-01-10XIAMEN DANGSHENG NEW MATERIAL CO LTD

Patent Information

Application Number
CN202410847866.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-01-10
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

The existing flash non-woven fabrics have shortcomings in mechanical strength and waterproofing properties, and have low reuse rates, especially in the field of medical protection, which is difficult to evaluate the residual amount after disinfection gas treatment.

Method used

Polymethylpentene, polylactic acid, epoxy resin, styrene-ethylene-butene-styrene block copolymer and modified calcium carbonate as components, and the surface hydroxyl group of modified calcium carbonate is adjusted by adjusting the component ratio and the surface hydroxyl group of modified calcium carbonate. The content forms excellent breathability, mechanical strength and waterproofing properties, and the starch-modified calcium carbonate avoids performance degradation caused by pickling treatment.

Benefits of technology

Flash non-woven fabrics with high breathability, mechanical strength and waterproof performance have been achieved, which has improved its reuse rate and ethylene oxide analysis efficiency in the medical packaging field, reduced the residual amount of disinfection gas, and improved the rational utilization of resources. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287585A_ABST
    Figure CN119287585A_ABST
Patent Text Reader

Abstract

The invention relates to a flash non-woven fabric and a preparation method and application thereof, and belongs to the technical field of high polymer materials. The flash non-woven fabric provided by the invention is prepared from the following components in parts by mass: 60 to 90 parts of polymethylpentene, 4 to 15 parts of polylactic acid, 4 to 10 parts of epoxy resin, 1 to 5 parts of styrene-ethylene-butylene-styrene block copolymer and 2 to 10 parts of modified calcium carbonate, the surface hydroxyl content of the modified calcium carbonate is more than or equal to 10 / nm < 2 > and less than or equal to 50 / nm < 2 >. The flash non-woven fabric provided by the invention has excellent mechanical properties, air permeability and ethylene oxide desorption performance, and is high in repeated utilization rate when being applied to preparation of medical instrument packaging products. Meanwhile, the flash non-woven fabric provided by the invention is wide in raw material source and beneficial to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a flash-steamed nonwoven fabric and a preparation method and application thereof. Background Art

[0002] Flash non-woven fabric is a new type of polymer breathable waterproof material, which can effectively block the passage of water while allowing gas to pass through. The main reason is that the surface of the flash non-woven fabric can form evenly distributed micropores, thus achieving excellent breathability.

[0003] Currently, pores are mainly formed by introducing calcium carbonate. Although the introduction of calcium carbonate can form a microporous structure to a certain extent, the post-processing is relatively complicated and requires further acid washing. In addition, due to the poor compatibility of calcium carbonate with the polymer resin matrix, the mechanical strength and waterproof properties of the obtained flash-steamed non-woven fabric will be reduced to a certain extent.

[0004] In addition, the existing flash-steamed non-woven fabrics are mostly used in the field of medical protection. In order to improve the rational and effective use of resources, reuse is generally considered. However, due to the particularity of the medical protection field, disinfection gas is generally used for treatment before reuse. Therefore, the residual amount after disinfection gas treatment is also a key indicator for evaluating whether it can be reused. Summary of the invention

[0005] The purpose of the present application is to overcome the shortcomings of the prior art and to provide a flash-steamed non-woven fabric having high air permeability, high mechanical strength, excellent waterproof performance, high efficiency in the decomposition of ethylene oxide, and high reuse rate when used in the field of medical packaging, as well as a preparation method and application thereof.

[0006] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a flash-steamed nonwoven fabric, which comprises the following components in parts by weight: 60 to 90 parts of polymethylpentene, 4 to 15 parts of polylactic acid, 4 to 10 parts of epoxy resin, 1 to 5 parts of styrene-ethylene-butylene-styrene block copolymer, and 2 to 10 parts of modified calcium carbonate.

[0007] The surface hydroxyl content of modified calcium carbonate is greater than or equal to 10 / nm 2 And less than or equal to 50 / nm 2 .

[0008] The flash-steamed nonwoven fabric provided in the present application is obtained by selecting components in appropriate mass proportions and cooperating with each other. The obtained flash-steamed nonwoven fabric has excellent air permeability and waterproof properties, and the obtained flash-steamed nonwoven fabric has high mechanical strength and high reusability when subsequently applied in the field of medical packaging.

[0009] Specifically, the present application selects polymethylpentene as the matrix resin, and introduces polylactic acid and epoxy resin, wherein polylactic acid is also called polylactide, which is a polyester polymer obtained by using lactic acid as the main raw material polymer. The introduction of polylactic acid can destroy the regular structure of polymethylpentene to a certain extent, thereby effectively improving the rheological properties of the melt and the compatibility of the overall components, and can also refine the fiber diameter of the flash non-woven fabric formed, so that the fiber arrangement of the flash non-woven fabric is more compact, thereby effectively improving the mechanical properties of the flash non-woven fabric. The addition of epoxy resin can further cooperate with polylactic acid to improve the mechanical properties of the flash non-woven fabric. The epoxy group and benzene ring group in the epoxy resin can bond with the carbonyl and hydroxyl groups in the polylactic acid, and can also act with the unsaturated bonds in the polymethylpentene, thereby forming a strong binding force between the components, thereby improving the excellent mechanical properties of the flash non-woven fabric, and due to the bonding of the components, the affinity of the hydrophilic group to water can be reduced, thereby achieving good waterproof performance. The introduction of styrene-ethylene-butylene-styrene block copolymer (SEBS) can further improve the compatibility between components. The dispersed phase formed in the polymethylpentene, polylactic acid and epoxy resin system added in this application is moderate, thereby improving the comprehensive performance of the prepared flash non-woven fabric. The introduction of modified calcium carbonate with a specific surface hydroxyl content can have good dispersibility in the resin matrix. The excellent dispersibility not only makes the components more uniform, but also the modified calcium carbonate itself is not easy to agglomerate, thereby forming a large number of microporous structures. In addition, unlike the direct introduction of calcium carbonate, which requires acid washing, the surface of the modified calcium carbonate introduced in this application is modified with starch, which can avoid the weakening of the mechanical properties and waterproof properties of the product by conventional calcium carbonate, thereby making the prepared flash non-woven fabric have excellent comprehensive performance.

[0010] It should be noted that the test method for the surface hydroxyl content of modified calcium carbonate is obtained by testing using the Green's reagent method.

[0011] For example, the surface hydroxyl content of the modified calcium carbonate may be 10 / nm 2 , 12 / nm 2 , 14 / nm 2 , 16 / nm 2 , 18 / nm 2 , 20 / nm 2 , 22 / nm 2 , 24 / nm 2 , 26 / nm 2 , 28 / nm 2 、30 / nm 2 、32 / nm 2 、34 / nm 2 、36 / nm 2、38 / nm 2 , 40 / nm 2 , 42 / nm 2 , 44 / nm 2 , 46 / nm 2 , 48 / nm 2 , 50 / nm 2 The range value of one or both of them.

[0012] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the flash-steamed nonwoven fabric includes the following components in parts by weight: 70 to 80 parts of polyamide resin, 6 to 10 parts of polylactic acid, 6 to 8 parts of epoxy resin, 3 to 4 parts of styrene-ethylene-butylene-styrene block copolymer, and 6 to 8 parts of modified calcium carbonate.

[0013] The present application study found that the mass fraction of the components of the flash-steamed nonwoven fabric will have a significant impact on the comprehensive performance of the product. When the mass fraction of the components of the flash-steamed nonwoven fabric is further selected to be within the above range, the comprehensive performance of the obtained flash-steamed nonwoven fabric is more excellent.

[0014] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the surface hydroxyl content of the modified calcium carbonate is greater than or equal to 20 / nm 2 And less than or equal to 30 / nm 2 .

[0015] The present application study found that the surface hydroxyl content of modified calcium carbonate affects the air permeability and the desorption efficiency of ethylene oxide of flash nonwoven fabrics. When the surface hydroxyl content of modified calcium carbonate is further selected to be greater than or equal to 20 / nm 2 And less than or equal to 30 / nm 2 When the flash-steamed nonwoven fabric is used, the comprehensive performance is better.

[0016] As a preferred embodiment of the flash non-woven fabric of the present application, the preparation method of modified calcium carbonate includes the following steps: adding starch and stirring after introducing carbon dioxide into the calcium hydroxide slurry, then continuing to introduce carbon dioxide to react until the system is acidic, then adding an esterification modifier and a catalyst to carry out an in-situ esterification reaction, filtering, drying, and crushing after the reaction to obtain modified calcium carbonate.

[0017] Preferably, the stirring time for adding starch is 20 to 60 minutes.

[0018] Preferably, the esterification modifier includes at least one of n-hexanoic acid, n-decanoic acid and n-octanoic acid.

[0019] Preferably, the catalyst comprises transglutaminase and pyridine; the mass ratio of transglutaminase to pyridine is 1:(10-20).

[0020] Preferably, the temperature of the in-situ catalyst reaction is 45 to 70° C. and the time is 1 to 6 hours.

[0021] Preferably, the mass ratio of starch, esterification modifier and catalyst is 1:(0.08-0.12):(0.01-0.1).

[0022] Preferably, the mass ratio of calcium hydroxide to starch is 1:(0.1-0.2).

[0023] The present application has found that the modified calcium carbonate prepared by the preparation method provided by the present application is modified by adding starch, and an esterification modifier is introduced to graft the hydroxyl groups on the surface of starch or calcium carbonate, so that the modified calcium carbonate with a surface hydroxyl content within the range given in the present application can be effectively obtained. On the one hand, starch is selected for modification, and starch is also a polymer substance, which has a certain compatibility with other resin matrices. On the other hand, further treatment with an esterification modifier can reduce the hydroxyl content on the surface of calcium carbonate and starch, further improve the compatibility of the modified calcium carbonate with the resin matrix of the present application, increase the dispersibility of the system, and form a richer and more uniform microporous effect in the subsequent preparation process, thereby ensuring the air permeability of the flash non-woven fabric and the decomposition efficiency of ethylene oxide, and improving the comprehensive performance of the product.

[0024] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the melting point of the polylactic acid is greater than or equal to 165°C and less than or equal to 175°C.

[0025] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the melt index of the polylactic acid is greater than or equal to 9 g / 10 min and less than or equal to 18 g / 10 min.

[0026] It should be noted that the test method for the melt index of polylactic acid is based on ASTM D1238, and the test conditions are 190° C. and 5 kg.

[0027] For example, the melting point of the polylactic acid may be any one of 165° C., 168° C., 170° C., 172° C., and 175° C., or any two of the range values. The melt index of the polylactic acid may be any one of 9 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, and 18 g / 10 min, or any two of the range values.

[0028] The present application has found that when polylactic acid with a melting point and a melt index within the range given in the present application is further selected, it has relatively excellent processing properties and mechanical properties, and has better compatibility with other components, thereby being able to effectively further improve the comprehensive performance of the flash-spun nonwoven fabric.

[0029] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the epoxy equivalent of the epoxy resin is greater than or equal to 180 g / eq and less than or equal to 190 g / eq.

[0030] It should be noted that the epoxy equivalent of the epoxy resin is tested using the acid value method.

[0031] Exemplarily, the epoxy equivalent of the epoxy resin may be any one or any two range values ​​of 180 g / eq, 181 g / eq, 182 g / eq, 183 g / eq, 184 g / eq, 185 g / eq, 186 g / eq, 187 g / eq, 188 g / eq, 189 g / eq, and 190 g / eq.

[0032] The present application has found that the epoxy equivalent of the epoxy resin will affect the bonding ability between the epoxy resin and polymethylpentene and polylactic acid, thereby affecting the comprehensive performance of the product. When the epoxy equivalent of the epoxy resin is further selected within the range given in the present application, the mechanical properties, air permeability and analytical performance of the obtained flash-steamed non-woven fabric are more excellent.

[0033] As a preferred embodiment of the flash-spun nonwoven fabric of the present application, a 10 mass % toluene solution of a styrene-ethylene-butylene-styrene block copolymer has a viscosity greater than or equal to 480 cp and less than or equal to 600 cp.

[0034] It should be noted that the test method for the viscosity of a 10 mass % toluene solution of a styrene-ethylene-butylene-styrene block copolymer is carried out in accordance with ASTM D2196.

[0035] For example, the viscosity of a 10 mass % toluene solution of the styrene-ethylene-butylene-styrene block copolymer may be in the range of any one or any two of 480 cp, 500 cp, 520 cp, 540 cp, 560 cp, 580 cp, and 600 cp.

[0036] The present application has found that styrene-ethylene-butylene-styrene block copolymer can effectively enhance the compatibility between polymethylpentene, polylactic acid and epoxy resin, and can also effectively improve the dispersibility of modified calcium carbonate in the system and enhance the microporous effect of subsequent performance, especially when the viscosity of 10% by mass toluene solution of styrene-ethylene-butylene-styrene block copolymer is further selected within the range given in the present application, the comprehensive performance of the obtained flash non-woven fabric is more excellent.

[0037] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the air permeability of the flash-steamed nonwoven fabric is greater than or equal to 30.0 mm / s and less than or equal to 50.0 mm / s according to GB / T5453 standard.

[0038] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the flash-steamed nonwoven fabric has a puncture resistance greater than or equal to 7000 J / m according to GB / T 8809 standard. 2 And less than or equal to 10000J / m 2 .

[0039] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the flash-steamed nonwoven fabric has a hydrostatic pressure resistance greater than or equal to 10989 Pa according to GB / T 4744 standard.

[0040] In a second aspect of the present application, the present application provides a method for preparing a flash nonwoven fabric, the preparation method comprising the following steps:

[0041] The components are added into a mixing device containing a solvent, and then heated and nitrogen is introduced so that the temperature in the mixing device is greater than or equal to 200° C. and less than or equal to 230° C., and the pressure is greater than or equal to 10 MPa and less than or equal to 12 MPa, to obtain a spinning solution;

[0042] The spinning solution is placed in a flash spinning device for spinning and received by a receiving device to form a film. The obtained fiber film is cold pressed and hot rolled to obtain a flash non-woven fabric.

[0043] Preferably, the boiling point of the solvent is ≤ 100°C.

[0044] More preferably, the solvent includes at least one of benzene, toluene, butane, pentene, n-hexane, heptane, octane, cyclohexane, dichloromethane, carbon tetrachloride, chloroform, chloromethane, chlorofluoromethane, and ethyl chloride.

[0045] More preferably, the mass ratio of the solid phase to the liquid phase in the spinning solution is (10-30):(70-90).

[0046] More preferably, the flash spinning device is prepared using the production equipment 300 used by the inventor in the prior research and development technology CN115323628B.

[0047] It should be noted that the products of the present application are not limited to the production of the above-mentioned production equipment. Technical personnel in this field may also adopt other types of flash production equipment to produce products according to actual needs, as long as products with the same technical characteristics and technical effects can be prepared.

[0048] In the third aspect of the present application, the present application provides the use of flash-steamed nonwoven fabric in the preparation of medical device packaging products.

[0049] Preferably, the medical device packaging product includes at least one of a packaging bag and an edge-sealed bag.

[0050] More preferably, the medical device packaging product comprises the flash-steamed non-woven fabric of the present application, which is combined in the medical device packaging product by at least one of means including but not limited to embedding, bonding or heat sealing, and can be arranged in the central area or the edge area, or can be arranged in the entire plane.

[0051] More preferably, the flash-spun nonwoven fabric is disposed inside or outside the packaging bag or the side-sealed bag.

[0052] More preferably, the flash-steamed nonwoven fabric is disposed in the middle or edge of the packaging bag or the side-sealed bag.

[0053] More preferably, the flash nonwoven fabric is disposed on a single plane or two planes of the packaging bag or the side-sealed bag.

[0054] More preferably, calculated based on the proportion of single-sided plane area, the flash-steamed non-woven fabric accounts for greater than or equal to 8% and less than or equal to 60% of the plane area of ​​the medical device packaging product.

[0055] Specifically, the plane area proportion of the flash-steamed non-woven fabric in the medical device packaging product can be 8%, 8.5%, 9%, 10%, 10.34%, 10.6%, 15%, 20%, 25%, 50%, 55%, 59%, 60% or any two of the range values.

[0056] It should be noted that the plane area refers to the total area of ​​the plane after the medical device packaging product is unfolded into a single plane. For example, a medical device packaging product is actually a plastic bag formed by symmetrically heat-bonding two flat plastic films, and one side of the plastic bag is open. The plane area of ​​the plastic bag is the sum of the plane areas of the two plastic films after they are unfolded.

[0057] Exemplarily, the medical device packaging product may be a sealed bag, which is formed by thermally bonding two rectangular planes, a first plane and a second plane. A breathable rectangular flash-steamed non-woven fabric is arranged at the central position of the first plane, and other positions are low-permeability or non-breathable sealing plastics; the rectangular flash-steamed non-woven fabric extends to the edge of the first plane of the sealing bag, so the length is the same as that of the first plane, the width of the flash-steamed non-woven fabric is 3 cm, and the length of the first plane is 14.5 cm; the second plane is exactly the same size as the first plane and the second plane is not provided with a flash-steamed non-woven fabric.

[0058] Therefore, the length of the two planes is defined as X cm, and the plane area ratio of the sealed bag is calculated as 3X / (2×14.5X)×100%=10.34%.

[0059] Exemplarily, the medical device packaging product may be a sealed bag, which is formed by thermally bonding two rectangular planes, a first plane and a second plane, wherein a breathable rectangular flash-steamed non-woven fabric is provided on the edge of the first plane, and low-permeability or non-breathable sealing plastic is provided in other positions; the width of the rectangular flash-steamed non-woven fabric is the same as that of the plane; the second plane is the same size as the first plane and is not provided with a flash-steamed non-woven fabric.

[0060] Exemplarily, the medical device packaging product may be a heat-sealed bag, which is obtained by combining two rectangular planes, a first plane and a second plane, by heat sealing, wherein the first plane is a flash-steamed non-woven fabric, and the second plane is a low-permeability or non-permeable sealing plastic, and the two planes have the same size. Therefore, based on the proportion of the plane area of ​​the heat-sealed bag, the flash-steamed non-woven fabric accounts for 50% of the plane area of ​​the side-sealed bag.

[0061] The flash-steamed nonwoven fabric described in the present application can be well applied to medical device packaging products that need to be sterilized with ethylene oxide gas but must ensure rapid ethylene oxide resolution capabilities based on its excellent air permeability efficiency and performance. Regardless of whether the sterilized body is a medical device or the packaging product itself, it has the ability to reach the ethylene oxide residual standard faster than existing packaging products. Based on this ability, technicians in this field can, according to actual needs, only use flash-steamed nonwoven fabrics with a minimum area share of 8% in the product (the air permeable components of existing packaging products generally account for 10% or more of the area) as air permeable resolution components, which can greatly save costs while ensuring resolution efficiency and performance, with high economic benefits.

[0062] Compared with the prior art, this application has the following advantages:

[0063] The flash nonwoven fabric provided by the present application is characterized by high air permeability, high mechanical strength, and excellent waterproof performance by selecting components of appropriate mass parts, and the components cooperate with each other. The flash nonwoven fabric obtained can be effectively applied to the field of medical device packaging. When applied to the field of medical device packaging, the flash nonwoven fabric itself has the characteristics of high ethylene oxide resolution efficiency, so it has a high reusability rate in specific applications. In addition, the raw materials of the flash nonwoven fabric provided by the present application are widely available, and the preparation method is simple to operate, which is conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a physical picture of a packaging bag product for medical device packaging further prepared from the flash-steamed non-woven fabric described in this application, wherein the white part is the flash-steamed non-woven fabric described in this application. DETAILED DESCRIPTION

[0065] To better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific examples. Other materials, reagents, etc. used in the examples, unless otherwise specified, can be obtained from commercial sources.

[0066] Polymethylpentene: RT180FG, Mitsui Chemicals,

[0067] Polylactic acid 1: FY602, melting point 165℃, melt index 9g / 10min, Fengyuan Bio,

[0068] Polylactic acid 2: FY401, melting point 175°C, melt index 18g / 10min, Fengyuan Bio,

[0069] Polylactic acid 3: FY802, melting point 165℃, melt index 4g / 10min, Fengyuan Bio,

[0070] Polylactic acid 4: FY201, melting point 175°C, melt index 30g / 10min, Fengyuan Bio,

[0071] Epoxy resin 1: YD-115, epoxy equivalent weight 185g / eq, Guodu Chemical,

[0072] Epoxy resin 2: YD-112, epoxy equivalent weight 175g / eq, Guodu Chemical,

[0073] Epoxy resin 3: YD-115CA, epoxy equivalent weight 205g / eq, Guodu Chemical,

[0074] SEBS-1: SEBS G1654 HU, 10 mass% toluene solution viscosity 480cp, Kraton Performance Polymers,

[0075] SEBS-2: YH-502, 10 mass% toluene solution viscosity is 600cp, Baling Petrochemical,

[0076] SEBS-3: YH-504, 10 mass% toluene solution viscosity is 670cp, Baling Petrochemical,

[0077] SEBS-4: YH-501, 10 mass% toluene solution viscosity is 450cp, Baling Petrochemical,

[0078] Modified calcium carbonate 1: surface hydroxyl content is 20 / nm 2 ,self made,

[0079] Modified calcium carbonate 2: surface hydroxyl content is 30 / nm 2 ,self made,

[0080] Modified calcium carbonate 3: surface hydroxyl content is 10 / nm 2,self made,

[0081] Modified calcium carbonate 4: surface hydroxyl content is 50 / nm 2 ,self made,

[0082] Modified calcium carbonate 5: surface hydroxyl content is 5 / nm 2 ,self made,

[0083] Modified calcium carbonate 6: surface hydroxyl content is 100 / nm 2 ,self made,

[0084] The preparation method of modified calcium carbonate 1 comprises the following steps:

[0085] A calcium hydroxide slurry with a mass concentration of 8% is added to a carbonization reactor, and carbon dioxide is introduced for carbonization reaction. When the conductivity drops to 3mS / cm, the introduction of carbon dioxide is stopped and starch (the mass percentage of starch is 15% based on calcium hydroxide) is added. After stirring for 30 minutes, carbon dioxide is continued to react and the pH value of the system is monitored. The reaction is stopped when the pH value of the system is less than 7 to obtain a calcium carbonate suspension. The temperature is then raised to 60°C and octanoic acid, transglutaminase and pyridine are added to react for 2 hours (based on starch, the mass percentage of octanoic acid is 10%, the mass percentage of transglutaminase is 0.5%, and the mass percentage of pyridine is 5%). After the reaction is completed, the mixture is filtered, the solid is collected, dried, crushed and sieved to obtain modified calcium carbonate 1.

[0086] The preparation of modified calcium carbonates 2 to 6 is to achieve the preparation of modified calcium carbonates with different surface hydroxyl contents by changing the mass percentage of starch, reaction temperature and time, and the addition amounts of n-octanoic acid, glutamine transaminase and pyridine.

[0087] Examples 1-14 and Comparative Examples 1-8

[0088] The present application example and comparative example provide a flash-steamed nonwoven fabric, and the components (by mass) of the flash-steamed nonwoven fabric are shown in Table 1-2.

[0089] Table 1

[0090]

[0091]

[0092] Table 2

[0093]

[0094]

[0095] The method for preparing the flash nonwoven fabric provided in Example 1 comprises the following steps:

[0096] (1) Preparation of masterbatch: polymethylpentene, polylactic acid, epoxy resin, styrene-ethylene-butylene-styrene block copolymer and modified calcium carbonate are mixed, and then transferred into a twin-screw extruder for melt extrusion and granulation at 90-180° C. to obtain masterbatch. The temperature of the twin-screw extruder is set as follows: 90-110° C. in zone 1, 120-130° C. in zone 2, 150-160° C. in zone 3, 170-180° C. in zone 4, 170-185° C. in zone 5, 170-185° C. in zone 6, 160-165° C. in zone 7, 160-165° C. in zone 8, 160-165° C. in zone 9, and 160-165° C. in zone 10. The screw speed of the twin-screw extruder is 180-220 rpm.

[0097] (2) Preparation of spinning solution: The masterbatch was transferred to a reactor containing a mixed solvent of difluorochloromethane and tetrafluorodichloroethane (15%:85%), preheated to 180°C, then nitrogen was introduced and pressurized to 12 MPa, and finally heated to 225°C and stirred in a closed manner for 2 h. After the temperature stabilized, a spinning solution was obtained. The mass ratio of the solid phase to the liquid phase in the spinning solution was 15:85.

[0098] (3) Preparation of flash nonwoven fabric: Referring to CN115323628B, a flash spinning device 300 was used to transfer the spinning solution to the nozzle for spray spinning, and then the spinning solution was refracted and reflected by a rotating filament separator to form a mesh and laid on a moving mesh curtain. The speed of the ejected air flow was 12000 m / min, the frequency of the rotating filament separator was 35 Hz, and the forward speed of the moving mesh curtain was 45 m / min. The collected mesh was cold pressed at a pressure of 0.5 to 1 MPa and hot rolled at a pressure of 140°C and 3 to 3.5 MPa (the hot rolling roller surface speed was 45 to 50 m / min) to obtain a flash nonwoven fabric with a thickness of about 0.12 mm.

[0099] The preparation methods of the flash-steamed nonwoven fabrics provided in Examples 2 to 13 and Comparative Examples 1 to 8 are consistent with the preparation method in Example 1.

[0100] Effect example

[0101] The effect example of the present application verifies the performance of the flash-steamed nonwoven fabrics prepared in Examples 1 to 14 and Comparative Examples 1 to 8, comprising the following steps:

[0102] (1) Air permeability performance: Tested according to GB / T 5453 (area 20cm 2 , pressure difference 200Pa),

[0103] (2)Puncture resistance: Tested in accordance with GB / T 8809.

[0104] (3) Hydrostatic pressure resistance: Tested in accordance with GB / T 4744 (pressure increase rate 6 kPa / min).

[0105] (4) Ethylene oxide desorption performance: The products of each embodiment and comparative example (total area 20 cm 2 ) and commercially available polypropylene film were prepared by hot pressing. Figure 1 The middle-sealed bag shown in the figure has a flash non-woven fabric that accounts for 20% of the plane area of ​​the middle-sealed bag. The middle-sealed bag is then sterilized with reference to GB / T 18279, wherein the sterilization parameters are: ethylene oxide concentration of 725ppm, maximum temperature of 55°C, maximum relative humidity of 60%, and contact time with ethylene oxide of 8h. The bag is left to stand for 24h at 50°C and 20% relative humidity, and then the ethylene oxide residue in the product is tested by gas chromatography.

[0106] The test results are shown in Table 3;

[0107] Table 3

[0108]

[0109]

[0110] It can be seen from Table 3 that when the technical solution provided by the present application is adopted, the obtained flash-steamed nonwoven fabric has excellent air permeability, mechanical strength, waterproofness and reusability. Specifically, the air permeability of the obtained flash-steamed nonwoven fabric is above 43.0 mm / s, and the puncture resistance is 70120 J / m 2 The above, the hydrostatic pressure resistance is above 10989Pa, and the ethylene oxide residue is below 7.3μg / g.

[0111] It can be seen from Examples 1 to 3 and Comparative Examples 1 to 2 that the mass fraction of the components in the flash nonwoven fabric will have a significant impact on the performance of the product. When the mass fraction of the modified calcium carbonate in Comparative Examples 1 to 2 is not within the range given in the present application, the air permeability, waterproof performance or mechanical properties of the obtained product are reduced to a certain extent, and the decomposition efficiency of the obtained product for ethylene oxide gas also shows a significant downward trend. This is because when the modified calcium carbonate is too little, the microporous structure cannot be effectively formed, resulting in a decrease in the air permeability of the product, and then the decomposition efficiency of ethylene oxide is also significantly reduced. At the same time, when the modified calcium carbonate is too much, although a better microporous structure will be formed to maintain a relatively good air permeability of the product, the mechanical properties and waterproof properties of the product will be reduced to a certain extent. In addition, due to the addition of too much micropores, the adsorption capacity of ethylene oxide is stronger, which leads to a certain downward trend in the subsequent ethylene oxide decomposition efficiency.

[0112] It can be seen from Example 1 and Examples 4 to 6, Example 1 and Examples 7 to 8, and Example 1 and Examples 9 to 11 that the specific selection of the melting point and melt index of the polylactic acid, the epoxy equivalent of the epoxy resin, and the viscosity of the SEBS 10 mass % toluene solution will also have an impact on the comprehensive performance of the product. When the parameters of the above components are further selected within the range specified in this application, the comprehensive performance of the obtained product is better.

[0113] It can be seen from Example 1, Examples 9 to 14 and Comparative Examples 3 to 5 that the surface hydroxyl content of modified calcium carbonate will also affect the performance of the product. When the surface hydroxyl content of modified calcium carbonate in Comparative Examples 3 to 4 is not within the given range, the decomposition efficiency of the obtained product for ethylene oxide is significantly reduced. When unmodified calcium carbonate is used in Comparative Example 5, the corresponding technical effect of the present application cannot be achieved.

[0114] It can be seen from Example 1 and Comparative Examples 6 to 8 that when the components of the present application are not added or are replaced by other types of components, the comprehensive performance of the obtained product is also significantly reduced.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A flash-steamed nonwoven fabric, characterized in that: The flash nonwoven fabric comprises the following components in parts by weight: 60 to 90 parts of polymethylpentene, 4 to 15 parts of polylactic acid, 4 to 10 parts of epoxy resin, 1 to 5 parts of styrene-ethylene-butylene-styrene block copolymer, and 2 to 10 parts of modified calcium carbonate; The surface hydroxyl content of the modified calcium carbonate is greater than or equal to 10 / nm 2 And less than or equal to 50 / nm 2 .

2. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The flash-steamed nonwoven fabric comprises the following components in parts by weight: 70-80 parts of polyamide resin, 6-10 parts of polylactic acid, 6-8 parts of epoxy resin, 3-4 parts of styrene-ethylene-butylene-styrene block copolymer, and 6-8 parts of modified calcium carbonate.

3. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The surface hydroxyl content of the modified calcium carbonate is greater than or equal to 20 / nm 2 And less than or equal to 30 / nm 2 .

4. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The preparation method of modified calcium carbonate comprises the following steps: introducing carbon dioxide into calcium hydroxide slurry, adding starch and stirring, then continuing to introduce carbon dioxide to react until the system is acidic, then adding an esterification modifier and a catalyst to carry out an in-situ esterification reaction, filtering, drying and crushing after the reaction is completed to obtain modified calcium carbonate.

5. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The melting point of the polylactic acid is greater than or equal to 165° C. and less than or equal to 175° C.; And / or, the melt index of the polylactic acid is greater than or equal to 9 g / 10 min and less than or equal to 18 g / 10 min.

6. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The epoxy equivalent of the epoxy resin is greater than or equal to 180 g / eq and less than or equal to 190 g / eq; And / or, the viscosity of a 10 mass % toluene solution of the styrene-ethylene-butylene-styrene block copolymer is greater than or equal to 480 cp and less than or equal to 600 cp.

7. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The air permeability of the flash nonwoven fabric is greater than or equal to 30.0 mm / s and less than or equal to 50.0 mm / s according to GB / T5453 standard; And / or, the flash nonwoven fabric has a puncture resistance of greater than or equal to 7000 J / m according to GB / T 8809 standard 2 And less than or equal to 10000J / m 2 ; And / or, the flash-steamed nonwoven fabric has a hydrostatic pressure resistance greater than or equal to 10989 Pa according to GB / T 4744 standard.

8. The method for preparing a flash-steamed nonwoven fabric according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The components are added into a mixing device containing a solvent, and then heated and nitrogen is introduced so that the temperature in the mixing device is greater than or equal to 200° C. and less than or equal to 230° C., and the pressure is greater than or equal to 10 MPa and less than or equal to 12 MPa, to obtain a spinning solution; The spinning solution is placed in a flash spinning device for spinning and received by a receiving device to form a film. The obtained fiber film is cold pressed and hot rolled to obtain a flash non-woven fabric.

9. Use of the flash-steamed nonwoven fabric according to any one of claims 1 to 7 in the preparation of medical device packaging products.

10. The use according to claim 9, characterized in that: The medical device packaging product comprises at least one of a packaging bag and an edge-sealed bag, the medical device packaging product comprises the flash-steamed nonwoven fabric according to any one of claims 1 to 7, and the plane area of ​​the flash-steamed nonwoven fabric in the medical device packaging product accounts for greater than or equal to 8% and less than or equal to 60%; Preferably, the flash-steamed nonwoven fabric is incorporated into the medical device packaging product by at least one of embedding, bonding, and heat sealing.

Citation Information

Patent Citations

  • High-shock-resistance polylactic acid composite material, preparation thereof and use thereof

    CN101275011A

  • Heavy calcium carbonate modifier, modification method of heavy calcium carbonate, modified heavy calcium carbonate and application of modified heavy calcium carbonate

    CN110183876A

  • Surface modification method of nano calcium carbonate with particle size of less than 20nm

    CN112480714A

  • Flash non-woven fabric and preparation method thereof

    CN114990787A

  • Reinforced and toughened polylactic acid composite material as well as preparation method and application thereof

    CN116875009A

Cited By

  • Working solution flash dehydration system and method in process of preparing hydrogen peroxide by anthraquinone process

    CN120607225A